Meconium Plug - Kshirsagar, Vinayak Yadavrao; Ahmed, Minhajuddin; Colaco, Sylvia Michael; Patil, Shriganesh (Journal of Nepal Paediatric Society, 2013)
Meconium plug presenting as intestinal obstruction in a full term neonate. DOI: http://dx.doi.org/10.3126/jnps.v33i3.8033 J. Nepal Paediatr. Soc. 2013;33(3):243-244